Gas-Solid Reaction Properties of Fluorine Compounds and Solid Adsorbents for Off-Gas Treatment from Semiconductor Facility. (8th August 2012) - Yasui, Shinji; Shojo, Tadashi; Inoue, Goichi; Koike, Kunihiko; Takeuchi, Akihiro; Iwasa, Yoshio
Abstract : We have been developing a new dry-type off-gas treatment system for recycling fluorine from perfluoro compounds present in off-gases from the semiconductor industry. The feature of this system is to adsorb the fluorine compounds in the exhaust gases from the decomposition furnace by using two types of solid adsorbents: the calcium carbonate in the upper layer adsorbs HF and converts it to CaF2, and the sodium bicarbonate in the lower layer adsorbs HF and SiF4 and converts them to Na2 SiF6 . This paper describes the fluorine compound adsorption properties of both the solid adsorbents—calcium carbonate and the sodium compound—for the optimal design of the fixation furnace. An analysis of the gas-solid reaction rate was performed from the experimental results of the breakthrough curve by using a fixed-bed reaction model, and the reaction rate constants and adsorption capacity were obtained for achieving an optimal process design.